Formulasi dan Uji Aktivitas Antibakteri Sediaan Emulgel Minyak Biji Jintan Hitam (Nigella sativa L.) terhadap Bakteri Staphylococcus epidermidis - Agistia, Nesa; Oktaviani, Melzi; Mukhtadi, Wildan Khairi; Ariska, Della (Jurnal Kefarmasian Indonesia, 2021)
Acne is a skin problem that often occurs, one of the causes is the bacterium Staphylococcus epidermidis. Black cumin seed oil (Nigella sativa L.) can be used as an antibacterial because it contains thymoquinone and α-pinene. This study aims to obtain black cumin seed oil emulgel preparations that has antibacterial activity against Staphylococcus epidermidis. The preparations were formulated with concentrations of 3% (FI), 5% (FII), and 7% (FIII). Evaluation of the preparation was carried out for eight weeks including organoleptic tests, spreadability, emulsion type, pH, viscosity, homogeneity. Antibacterial activity tests was carried out using the well-diffusion method. The results of the evaluation of all three formulas obtained showed a semi-solid consistency, light brown in color, characteristically smelled of black cumin seed oil, stable, M/A emulsion type, homogeneous, non-irritating, pH FI = 4.51-4.95, FII = 4.72-4.99, FIII = 4.57-4.87, dispersion FI = 3.2-3.8 cm, FII = 3.3-3.9 cm, FIII = 3.4-3.9 cm, viscosity FI = 10.7-26.1 Ns/m2, FII = 11.2-32.0 Ns/m2, FIII = 11.5-34.1 Ns/m2. The antibacterial activity test showed the inhibitory power of FI 11,66±0,09 mm, FII 14.48±0.03 mm, FIII 17.35±0,.8 mm, lower than the positive control (clindamycin). All three black cumin seed oil emulgel preparations obtained met the physical requirements and had bacterial inhibition (p